The use of megaprosthesis in elderly patients: a case series - Mosconi, Mario; Jannelli, Eugenio; Castelli, Alberto; Pasta, Gianluigi; Ivone, Alessandro (Lo Scalpello - Journal, 2021)
Objective. Herein, we present a case series of patients treated with megaprosthesis who sustained high energy trauma with comminuted articular hip or knee fracture, complex periprosthetic fractures or pathological fractures. Methods. We retrospectively reviewed 15 consecutive patients who sustained knee re- placement/revision (7 patients) and 8 patients who underwent hip replacement/revision with megaprosthesis between 2014 and 2018. In the knee group, there was 1 man and 6 women, while in the hip group there were 3 men and 5 women. In knee group, preoperative indications were: periprosthetic fracture; highly comminuted distal femoral fracture; metastatic localization of distal femur; nonunion of distal femoral fracture in one case. In the hip group, preoperative indications were: subtrochanteric pathological fractures; peri- prosthetic fracture; recurrent infection; recurrent tumoral lesions. Preoperative evaluation included standard radiographs; CT-scan with 3D reconstruction for tailored implant planning; MRI only for pathological localization. Results. Mean clinical follow-up with radiographic control was 44 months (range 23-71). All complications were managed before the patient left the hospital. During the follow-up period, 13 of 15 patients regained walking ability as before surgery. At the end of follow-up, 6 patients had died due to causes not related to the surgery. Conclusions. The use of megaprosthesis offers useful solutions for different pathologies such as tumors, infections, comminu ed fractures, and periprosthetic fractures in the elderly patient with good functional results.